Phylogeny and origins of chemosynthetic vesicomyid clams. Issue 4 (4th July 2017) - Johnson, Shannon B.; Krylova, Elena M.; Audzijonyte, Asta; Sahling, Heiko; Vrijenhoek, Robert C.
Abstract : Large vesicomyid clams (Veneroida: Vesicomyidae: Pliocardiinae) are prominent members of the communities associated with sulphide-rich deep-sea habitats. Taxonomic uncertainties within the Pliocardiinae result from both plasticity in shell morphologies and the common occurrence of cryptic species. Molecular taxonomic studies have now clarified many species-level assignments and provided DNA-barcodes for more than 50 species worldwide. Nonetheless, genus-level assignments remain uncertain, because the existing COI barcode sequences are not sufficient for identifying higher-level groupings. To construct a robust phylogeny for this subfamily, we conducted a combined Bayesian analysis of the COI mitochondrial fragment and five additional independent nuclear gene segments. The phylogenetic results provide a better foundation for assessing genus-level assignments within the subfamily and reveal goals for future taxonomic research. Furthermore, morphological examinations helped to clarify and solidify generic classifications. Calibration of molecular clocks with recently verified fossil data permitted realistic estimates for the origins and evolutionary age of pliocardiins during the Cenozoic Era from a deep-dwelling ancestor. http://zoobank.org/urn:lsid:zoobank.org:pub:2554122D-96D4-4CBF-BC70-B017998AF64D